STUDY ON VARIABILITY OF OCEAN THERMAL ENERGY POTENTIAL IN THE EXCLUSIVE ECONOMIC ZONE OF INDONESIAN WATERS - Basardo Jonatan Sinaga, Denny
This study aims to estimate ocean thermal energy resources in Exclusive Economic Zone (EEZ) of Indonesian waters based on 50 years (from January 1964 to December 2013) monthly temperature data from simulation results of threedimensional hydrodynamic model Hybrid Coordinate Ocean Model (HYCOM) with a resolution of 0,125°. The area under study stretches from 6° N to 11° S and from 95° E to 139° E. The thermal energy recources in this study were calculated by temperature differences between water depth of 20 m and 1000 m. The results show that EEZ of Indonesia waters area of 3.495.698,72 km2 have the potential to develop OTEC with monthly average potential power as much 289,73 GW. The variability of ocean thermal energy potential shows that the highest monthly average potential power of ocean thermal energy is in December at 295,65 GW and the lowest in August at 280,09 GW. The highest seasonal average potential power of ocean thermal energy is in first transition season at 293,91 GW and the lowest in east monsoon season at 284,18 GW. The results also show that the highest annual average potential power of ocean thermal energy is in 1998 at 298,99 GW and the lowest in 1967 at 280,44 GW.